EFEKTIVITAS PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM TRANSAKSI E-COMMERCE DENGAN SISTEM CASH ON DELIVERY - Anhar Yasin Kurniawan; Mochammad Najib Imanullah (Jurnal Privat Law, 2026)
This article studies regarding effectiveness on consumer’s protection law on electronic purchases made with cash on delivery transaction method on ecommerce platform based on Indonesia consumer’s protection Law Number 8 of 1999, which mainly aims to give consumer a better protection as they are perceived being on the weaker side on electronic based transactions. This article is empirical legal research. The legal material type used are primary and secondary legal materials, as well as non-legal materials or tertiary legal materials. These legal materials are collected through legal documents acquired by downloading, copying, collecting and then reading, studying, reviewing and analyzing primary legal materials such as Law Number 8 of 1999, Kitab UndangUndang Hukum Perdata and other regulations, books, articles, journals and others by adjusting the problems studied by the author. Furthermore, the technical analysis used is the deduction method. The result shows that effectivity on consumer’s protection law on electronic transactions done on e-commerce platform remains ineffective based on majority of transactions done, dispute resolutions are considered time consuming and the transactions made consist mostly of small purchases for the consumer led to neglect on mentioned dispute resolution.